Clinical determinants of successful weaning from extracorporeal membrane oxygenation in patients with fulminant myocarditis. (14th May 2018) - Matsumoto, Manabu; Asaumi, Yasuhide; Nakamura, Yuichi; Nakatani, Takeshi; Nagai, Toshiyuki; Kanaya, Tomoaki; Kawakami, Shoji; Honda, Satoshi; Kataoka, Yu; Nakajima, Seiko; Seguchi, Osamu; Yanase, Masanobu; et al.
Abstract: Aims: Patients with fulminant myocarditis (FM) often present with cardiogenic shock and require mechanical circulatory support, including extracorporeal membrane oxygenation (ECMO) and ventricular assist device (VAD) implantation. This study sought to clarify the determinants of successful weaning from ECMO in FM patients. Methods and results: We studied 37 consecutive FM patients supported by ECMO as the initial form of mechanical circulatory support between January 1995 and December 2014 in our hospital. Twenty‐two (59%) patients were successfully weaned from ECMO, while 15 (41%) were not. There were significant differences in levels of peak creatine kinase and those of its MB isoform (CK‐MB), left ventricular posterior wall thickness (LVPWT), and prevalence of cardiac rhythm disturbances. Receiver operating characteristic curve analysis revealed that a peak CK‐MB level of 185 IU/L and LVPWT of 11 mm were the optimal cut‐off values for predicting successful weaning from ECMO (areas under the curve, 0.89 and 0.85, respectively). During the follow‐up [median 48 (interquartile range 8–147) months], 83% of FM patients who were weaned from ECMO survived, with preserved fractional shortening based on echocardiography. Of the 15 FM patients who were not weaned from ECMO, nine bridged to VAD, and only two were successfully weaned from VAD and survived. Conclusions: These results indicate that myocardial injury, as evidenced by CK‐MB and LVPWT, and prolonged presence of cardiac rhythm disturbances are important clinical determinants of successful weaning from ECMO.